Comparison of six-minute walk test in children with moderate/severe asthma with reference values for healthy children - Lívia Barboza de Andrade; Diogo A.R.G. Silva; Taíza L.B. Salgado; José N. Figueroa; Norma Lucena-Silva; Murilo C.A. Britto (Brazilian Society of Pediatrics, 2014)
Objective: to compare physical performance and cardiorespiratory responses in the six-minute walk test (6MWT) in asthmatic children with reference values for healthy children in the same age group, and to correlate them with intervening variables. Methods: this was a cross-sectional, prospective study that evaluated children with moderate/severe asthma, aged between 6 and 16 years, in outpatient follow-up. Demographic and spirometric test data were collected. All patients answered the pediatric asthma quality of life (QoL) questionnaire (PAQLQ) and level of basal physical activity. The 6MWT was performed, following the American Thoracic Society recommendations. Comparison of means was performed using Student's t-test and Pearson's correlation to analyze the 6MWT with study variables. The significance level was set at 5%. Results: 40 children with moderate or severe asthma were included, 52.5% males, 70% with normal weight and sedentary. Mean age was 11.3 ± 2.1 years, mean height was 1.5± 0.1 m, and mean weight was 40.8 ± 12.6 Kg. The mean distance walked in the 6MWT was significantly lower, corresponding to 71.9% ± 19.7% of predicted values; sedentary children had the worst values. The difference between the distance walked on the test and the predicted values showed positive correlation with age (r = 0.373, p = 0.018) and negative correlation with cardiac rate at the end of the test (r = -0.518, p < 0.001). Regarding QoL assessment, the values in the question about physical activity limitations showed the worst scores, with a negative correlation with walked distance difference (r= -0.311, p = 0.051). Conclusions: asthmatic children's performance in the 6MWT evaluated through distance walked is significantly lower than the predicted values for healthy children of the same age, and is directly influenced by sedentary life style.